Atomized Fe-Si-Al soft magnetic powder and preparation method thereof

By using FeSiAl alloy and high-pressure nitrogen atomization technology, combined with the use of slag removal agent and deoxidizer, the problem of slag oxidation and slag formation under non-vacuum conditions is solved, and the stable and efficient preparation of ferrosilicon aluminum soft magnetic powder is achieved, reducing the production costs.

CN119489195APending Publication Date: 2025-02-21JIANGMEN HONGJIA NEW MATERIAL TECH CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411675118.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-21
Publication Date
2025-02-21

AI Technical Summary

Technical Problem

Under non-vacuum conditions, due to the large gap in melting points of ferrosilicon aluminum, Al metal is prone to oxidation and slag production, which causes the aluminum slag to block the leak during aerosolization, affecting production efficiency and component stability.

Method used

FeSiAl alloy is used as raw material to prepare ferrosilicon aluminum soft magnetic powder through low-temperature smelting and high-pressure nitrogen atomization, and a slag removal agent and deoxidizing agent are added to control the oxygen content and remove aluminum slag.

Benefits of technology

It effectively avoids oxidation and slag production of aluminum elements, improves the stability and efficiency of the aerosolization process, reduces production costs, and obtains ferrosilicon aluminum soft magnetic powder with good spherical shape and low oxygen content.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119489195A_ABST
    Figure CN119489195A_ABST
Patent Text Reader

Abstract

The invention discloses aerosolized Fe-Si-Al soft magnetic powder and a preparation method thereof. The preparation method comprises the steps of proportioning, alloy smelting, aerosolized pulverization and sieving. According to the preparation method, the purposes of low-temperature smelting and low-temperature atomization are achieved by adopting a FeSiAl alloy, then the Fe-Si-Al soft magnetic alloy powder is prepared through high-pressure nitrogen atomization, and the problem that an aluminum element is oxidized to form slag due to different Fe-Si-Al melting points in a non-vacuum state can be solved; therefore, the problem that the gas atomization process cannot be continuously carried out due to the fact that the discharge spout is blocked by the aluminum slag is solved, the gas atomization process in a non-vacuum state is achieved, the problems that expensive vacuum equipment is used and complicated vacuumizing operation is carried out can be avoided, the production process is simple, the production efficiency is high, and the production cost can be greatly reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of powder metallurgy preparation, and in particular to a gas atomized sendust soft magnetic powder and a preparation method thereof. Background Art

[0002] At present, the conventional preparation methods of Sendust soft magnetic powder include mechanical crushing, water atomization and gas atomization. The magnetic properties of magnetic powder cores are closely related to the powder properties of the powder. The performance of Sendust powder prepared by different methods is very different. The powder prepared by mechanical crushing has an irregular shape, a high oxygen content, poor powder compressibility, and poor performance of the pressed powder core. The water atomization method has a large output and fine powder for preparing Sendust powder. The particles are irregular polygonal or nodular in shape, the particle surface is rough and uneven, and there are a certain amount of sharp corners, which is not conducive to insulation coating. The Sendust powder particles prepared by the gas atomization method have better effects, with good sphericity, low oxygen content and uniform chemical composition, and are suitable for insulation coating.

[0003] Gas atomization is divided into two processes: non-vacuum gas atomization and vacuum gas atomization. The vacuum gas atomization production method mainly uses high-pressure nitrogen to gas-atomize alloy melt to produce iron-silicon-aluminum powder. The advantages of the vacuum gas atomization production method are that the prepared iron-silicon-aluminum powder has a low oxygen content, the vacuum equipment is expensive, the production process is complicated, the production efficiency is low, and the product cost is high.

[0004] The non-vacuum gas atomization production method is relatively simple, but since the melting points of iron, silicon and aluminum in the metal raw materials are 1583°C, 1410°C and 660°C respectively, when the three metals are smelted into alloys under non-vacuum conditions, aluminum is easily oxidized and slag is formed in the melt, forming aluminum slag in the melt, causing the silicon and aluminum content to decrease, resulting in uncontrollable fluctuations in the composition of the Sendust soft magnetic powder, making the composition of each batch of Sendust soft magnetic powder unstable.

[0005] Therefore, the production method of non-vacuum gas atomization of iron-silicon-aluminum powder is difficult to operate and the composition control is difficult; and during the gas atomization process, aluminum slag will hinder the melt from entering the gas atomization chamber through the nozzle, causing the gas atomization process to easily become blocked, making it impossible for the production process to proceed normally, seriously affecting production efficiency. Summary of the invention

[0006] The purpose of the present invention is to provide a gas atomized iron silicon aluminum soft magnetic powder and a preparation method thereof, so as to solve the above-mentioned problem that Al metal is prone to oxidation and slagging under non-vacuum conditions due to the large difference in melting points between the metal raw materials.

[0007] To achieve this object, the present invention adopts the following technical solutions:

[0008] The present invention provides a method for preparing gas-atomized sendust soft magnetic powder, comprising the following steps:

[0009] Proportion: according to the proportion, weigh FeSiAl alloy raw material, slag remover and deoxidizer;

[0010] Alloy smelting: heating and smelting the FeSiAl alloy raw material, adding a slag remover and a deoxidizer, and stirring; after stirring, standing and removing the slag to obtain an alloy melt;

[0011] Gas atomization powder making: The alloy melt is poured into the tundish, and the alloy melt flows into the gas atomization chamber from the guide pipe at the bottom of the tundish. The alloy melt is atomized by high-pressure nitrogen gas, and the alloy melt is broken into droplets. After cooling and solidification, the droplets are precipitated to obtain semi-finished powder;

[0012] Sieving: After cooling to room temperature, the semi-finished powder is sieved to obtain aerosolized Sendust soft magnetic powder.

[0013] In the method for preparing the gas atomized sendust soft magnetic powder, in the proportioning step, the amount of the slag remover added is 0.15-0.35% of the total mass of the FeSiAl alloy raw material, and the amount of the deoxidizer added is 0.20-0.40% of the total mass of the FeSiAl alloy raw material.

[0014] In the method for preparing the gas-atomized sendust soft magnetic powder, the commercially available model of the deslagging agent is F2 deslagging agent, and the deoxidizing agent is calcium silicon particles.

[0015] In the method for preparing the gas-atomized sendust soft magnetic powder, in the step of alloy smelting, the alloy smelting temperature is 1600-1650° C., and the standing time is 0.5-2.5 min.

[0016] In the method for preparing the gas atomized sendust soft magnetic powder, in the gas atomization powder making step, the alloy melt pouring temperature is 1560-1620°C; the pressure of the high-pressure nitrogen is 4.0-5.0 MPa; and the temperature inside the tundish is 1200-1300°C.

[0017] In the method for preparing the gas atomized sendust soft magnetic powder, in the gas atomization powder making step, the material of the guide tube is boron nitride or zirconium oxide, and the diameter of the guide tube is 4.0 to 7.0 mm.

[0018] In the method for preparing the aerosolized Sendust soft magnetic powder, in the sieving step, the particle size of the aerosolized Sendust soft magnetic powder is 165-180 meshes.

[0019] In the method for preparing the gas-atomized FeSiAl soft magnetic powder, the FeSiAl alloy comprises the following components by weight percentage: 7-12% Si and 4-8% Al, with the remainder being Fe and other inevitable impurities.

[0020] The present invention also provides an aerosolized iron-silicon-aluminum soft magnetic powder, which is obtained by the above-mentioned preparation method of the aerosolized iron-silicon-aluminum soft magnetic powder. The iron-aluminum-silicon alloy comprises the following components by weight percentage: 6-11% Si and 4-8% Al, and the balance is Fe and other inevitable impurities, wherein the other inevitable impurities include C, Mn, P and S, and by weight percentage, the content of the C element is <0.010%, the content of the Mn element is <0.35%, the content of the P element is <0.03%, and the content of the S element is <0.01%.

[0021] A technical solution in the present invention can have the following beneficial effects:

[0022] The preparation method adopts FeSiAl alloy to achieve the purpose of low-temperature melting and low-temperature atomization, and then uses high-pressure nitrogen atomization to prepare the iron-silicon-aluminum soft magnetic alloy powder, which can overcome the problem of oxidation and slag formation of aluminum element due to the different melting points of iron-silicon-aluminum in a non-vacuum state, thereby avoiding the problem that the aluminum slag blocks the nozzle and the atomization process cannot continue, and realizes the atomization process in a non-vacuum state, which can avoid the problem of using expensive vacuum equipment and performing complicated vacuuming operations. The production process is simple and the production efficiency is high, which can greatly reduce the production cost. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 This is a microscopic morphology of the gas-atomized sendust soft magnetic powder obtained in Example 1 of the present invention;

[0024] Figure 2 This is a microscopic morphology of the gas-atomized sendust soft magnetic powder obtained in Example 2 of the present invention;

[0025] Figure 3 This is a microscopic morphology of the gas atomized sendust soft magnetic powder obtained in Example 3 of the present invention;

[0026] Figure 4 This is a microscopic morphology of the gas-atomized sendust soft magnetic powder obtained in Comparative Example 1 of the present invention;

[0027] Figure 5 This is a microscopic morphology of the gas atomized Sendust soft magnetic powder obtained in Comparative Example 2 of the present invention. DETAILED DESCRIPTION

[0028] The technical scheme of the present invention is further illustrated by specific embodiments below. In order to facilitate understanding of the present invention, the present invention is described more comprehensively below. The present invention can be implemented in many different forms and is not limited to the embodiments described herein. On the contrary, the purpose of providing these embodiments is to make the understanding of the disclosure of the present invention more thorough and comprehensive.

[0029] If no specific techniques or conditions are specified in the examples, the techniques or conditions described in the literature in the field or the product instructions are used. If no manufacturer is specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0031] The present invention provides a method for preparing gas-atomized sendust soft magnetic powder, comprising the following steps:

[0032] Proportion: according to the proportion, weigh FeSiAl alloy raw material, slag remover and deoxidizer;

[0033] Alloy smelting: heating and smelting the FeSiAl alloy raw material, adding a slag remover and a deoxidizer, and stirring; after stirring, standing and removing the slag to obtain an alloy melt;

[0034] Gas atomization powder making: The alloy melt is poured into the tundish, and the alloy melt flows into the gas atomization chamber from the guide pipe at the bottom of the tundish. The alloy melt is atomized by high-pressure nitrogen gas, and the alloy melt is broken into droplets. After cooling and solidification, the droplets are precipitated to obtain semi-finished powder;

[0035] Sieving: After cooling to room temperature, the semi-finished powder is sieved to obtain aerosolized Sendust soft magnetic powder.

[0036] In the alloy melting step, a non-vacuum induction furnace is used to melt the FeSiAl alloy raw material.

[0037] The preparation method of the gas-atomized iron-silicon-aluminum soft magnetic powder uses FeSiAl alloy as the raw material of the gas-atomized iron-silicon-aluminum soft magnetic powder. Due to the difference in atomic structure between Fe, Si and Al in the FeSiAl alloy, different elements in the alloy will disturb the arrangement of the metal lattice, weakening the bonding force between atoms. This lattice distortion causes the alloy to undergo phase change at a lower temperature, thereby reducing the melting point. Therefore, the melting point of the FeSiAl alloy is less than 1400°C, which is much lower than the melting points of Fe and Si. Using the FeSiAl alloy as the raw material of the gas-atomized iron-silicon-aluminum soft magnetic powder can reduce the melting temperature, reduce the oxidation of the Al element, and improve the smelting efficiency.

[0038] By adopting FeSiAl alloy, the purpose of low-temperature melting and low-temperature atomization is achieved, and then high-pressure nitrogen atomization is used to prepare iron-silicon-aluminum soft magnetic alloy powder. The problem of oxidation and slag formation of aluminum element caused by the different melting points of iron-silicon-aluminum in non-vacuum state can be overcome, thereby avoiding the problem of aluminum slag clogging the nozzle and causing the atomization process to be unable to continue, and realizing the atomization process in non-vacuum state.

[0039] The above-mentioned preparation method can avoid the use of expensive vacuum equipment and the problem of complicated vacuum pumping operations. The production process is simple and the production efficiency is high, which can greatly reduce the production cost. At the same time, the sphericity of the atomized iron silicon aluminum soft magnetic powder is good, the oxygen content can be controlled below 500ppm, and the yield rate can reach more than 80%.

[0040] Specifically, in the proportioning step, the amount of the slag remover added is 0.15-0.35% of the total mass of the FeSiAl alloy raw material, and the amount of the deoxidizer added is 0.20-0.40% of the total mass of the FeSiAl alloy raw material.

[0041] During the metal smelting process, Al metal has a low melting point and is easy to react with oxygen in the air to form oxides, namely aluminum slag. The deoxidizer can react with oxygen in the alloy melt to form compounds that are easy to remove. The slag remover is used to remove the aluminum slag during the smelting process, thereby avoiding the problem of aluminum slag blocking the pipeline and causing the atomization to be unable to continue.

[0042] If the amount of deoxidizer added is too much, the excess part cannot effectively participate in the reaction, resulting in a waste of resources, increased production costs, and affected product performance; while if the amount of deoxidizer added is too little, the oxygen in the alloy melt cannot be completely removed. The above amount of deoxidizer added can effectively remove oxygen in the alloy melt.

[0043] Too much slag remover will cause instability in the alloy composition, while too little slag remover will result in poor slag removal effect, causing aluminum slag to block the tundish and affect atomization efficiency. The above amount of slag remover can effectively remove aluminum slag during the smelting process.

[0044] Specifically, the commercially available model of the deslagging agent is F2 deslagging agent, and the deoxidizing agent is calcium silicon particles.

[0045] In a specific embodiment of the present invention, a commercially available F2 deslagging agent is used as a deslagging agent, and calcium silicon particles are used as a deoxidizer. In addition to effectively removing aluminum slag, the F2 deslagging agent also plays a role in inhibiting oxidation. The calcium silicon particles can quickly react with oxygen in the alloy melt to generate stable oxides, thereby effectively reducing the oxygen content in the alloy melt. In addition, the fluidity and stability of the alloy melt can be improved, and the viscosity of the aluminum slag can be reduced.

[0046] Specifically, in the step of alloy smelting, the alloy smelting temperature is 1600-1650° C., and the standing time is 0.5-2.5 min.

[0047] In a preferred embodiment of the present invention, the alloy smelting temperature is 1610-1640°C, which can effectively reduce the oxidation and slag increase of Al metal. Standing for 0.5-2.5 minutes can give the slag remover and deoxidizer enough time to react, thereby achieving the effect of slag removal and deoxidation.

[0048] Specifically, in the gas atomization powder making step, the pouring temperature of the alloy melt is 1560-1620°C; the pressure of the high-pressure nitrogen is 4.0-5.0 MPa; and the temperature inside the tundish is 1200-1300°C.

[0049] Since FeSiAl alloy is used as the raw material of gas atomized FeSiAl soft magnetic powder, the melting temperature is effectively reduced, so that the alloy melt can be poured at a temperature of 1560-1620°C. In a preferred embodiment of the present invention, the alloy melt pouring temperature is 1575-1610°C.

[0050] The above-mentioned high-pressure nitrogen pressure has high atomization efficiency, and the crushed alloy powder droplet product has high yield, good sphericity, and the finished product rate can reach more than 80%. In a preferred embodiment of the present invention, the pressure of the high-pressure nitrogen is 4.4-4.8MPa.

[0051] By adopting the above-mentioned temperature inside the tundish, the cooling and agglomeration of the alloy melt in the tundish due to the temperature drop can be reduced, thereby avoiding the blockage of the tundish.

[0052] Specifically, in the gas atomization powder making step, the material of the guide tube is boron nitride or zirconium oxide, and the diameter of the guide tube is 4.0-7.0 mm.

[0053] Boron nitride and zirconium oxide have good high temperature characteristics, and perform well in thermal shock stability and erosion resistance, so that the atomization process can be carried out stably, ensuring production efficiency and product performance. The use of the above-mentioned guide tube diameter can reduce the chance of the guide tube being blocked by aluminum slag. The preparation method of the gas-atomized iron-silicon-aluminum soft magnetic powder uses a guide tube to introduce the alloy melt into the gas atomization chamber. The diameter of the guide tube is 4.0 to 7.0 mm, the flux of the guide tube is larger, and it is less likely to be blocked.

[0054] Preferably, in the sieving step, the particle size of the atomized Sendust soft magnetic powder is 165-180 meshes.

[0055] In a specific embodiment of the present invention, the semi-finished powder after cooling is screened and graded, and the specific screening and grading methods can be ultrasonic vibration screening and airflow grading methods. By adopting the above steps, atomized sendust soft magnetic powder of suitable size can be screened out.

[0056] Specifically, the FeSiAl alloy comprises the following components by weight percentage: 7-12% Si and 4-8% Al, with the remainder being Fe and other inevitable impurities.

[0057] The atomized Sendust soft magnetic powder introduces non-magnetic elements silicon and aluminum, which increases the resistivity of the alloy, reduces the coercive force, reduces the magnetostriction coefficient, and reduces the saturation magnetization and magnetic loss. Other unavoidable impurities include C, Mn, P and S, which are common impurities in pure iron. The lower the content of other unavoidable impurities, the better the performance of the atomized Sendust soft magnetic powder, but the cost will also increase accordingly.

[0058] The present invention also provides an aerosolized iron-silicon-aluminum soft magnetic powder, which is obtained by the above-mentioned preparation method of the aerosolized iron-silicon-aluminum soft magnetic powder. The iron-aluminum-silicon alloy comprises the following components by weight percentage: 6-11% Si and 4-8% Al, and the balance is Fe and other inevitable impurities, wherein the other inevitable impurities include C, Mn, P and S, and by weight percentage, the content of the C element is <0.010%, the content of the Mn element is <0.35%, the content of the P element is <0.03%, and the content of the S element is <0.01%.

[0059] The aerosolized sendust soft magnetic powder prepared by the above method has good soft magnetic properties, and has the advantages of low price, high magnetic permeability, high resistivity, low coercivity, low loss, stable DC bias characteristics and good temperature stability.

[0060] Example 1

[0061] A method for preparing gas-atomized sendust soft magnetic powder comprises the following steps:

[0062] According to the proportion, FeSiAl alloy raw material, F2 slag remover and silicon-calcium particles are weighed; the FeSiAl alloy comprises the following components by weight percentage: 9.5% Si and 5.5% Al, the balance being Fe and other inevitable impurities, and the total content of impurity elements is less than 0.5%;

[0063] The FeSiAl alloy raw material is heated and melted in a non-vacuum induction furnace, and F2 deslagging agent and silicon-calcium particles are added and stirred; after stirring, the alloy is allowed to stand and slag is removed to obtain an alloy melt; wherein the melting temperature is 1625°C, the amount of F2 deslagging agent added is 0.35%, and the amount of silicon-calcium particles added is 0.30%; the alloy is allowed to stand for 1.25 minutes;

[0064] The alloy melt is poured into the tundish, and the alloy melt flows into the gas atomization chamber from the guide tube at the bottom of the tundish. The alloy melt is atomized by high-pressure nitrogen gas, and the alloy melt is broken into droplets. After cooling and solidification, the semi-finished powder is obtained by sedimentation. The alloy melt pouring temperature is 1595°C, the atomizing nitrogen pressure is 4.65MPa, the temperature inside the tundish is controlled at 1285°C, the guide tube is made of boron nitride, and the diameter of the guide tube is 5.5mm.

[0065] After the temperature drops to room temperature, the semi-finished powder is sieved using an ultrasonic vibration sieving machine with a 170-mesh sieve to obtain atomized sendustine soft magnetic powder.

[0066] Example 2

[0067] The preparation method of Example 2 is the same as that of Example 1, except that: 1. The FeSiAl alloy comprises the following components by weight: 9.6% Si and 5.4% Al, the remainder being Fe and other inevitable impurities, and the total content of impurity elements is <0.5%; 2. During heating and smelting, the smelting temperature is 1630°C; 3. The pouring temperature of the alloy melt is 1590°C, the atomizing nitrogen pressure is 4.60MPa, and the temperature inside the tundish is controlled at 1280°C.

[0068] Example 3

[0069] The preparation method of Example 3 is the same as that of Example 1, except that: 1. The FeSiAl alloy comprises the following components by weight: 9.7% Si and 5.5% Al, the remainder being Fe and other inevitable impurities, and the total content of impurity elements is <0.5%; 2. During heating and smelting, the smelting temperature is 1628°C; 3. The pouring temperature of the alloy melt is 1580°C, and the atomizing nitrogen pressure is 4.60MPa.

[0070] Comparative Example 1

[0071] A method for preparing gas-atomized sendust soft magnetic powder comprises the following steps:

[0072] According to the proportion, industrial pure iron of model YT01, industrial silicon of model #2202, aluminum ingot, F2 type slag remover and silicon-calcium particles are weighed and mixed to obtain a mixed raw material; by weight percentage, the content of Si is 9.5%, the content of Al is 5.5%, the balance is Fe and other inevitable impurities, and the total content of impurity elements is less than 0.5%;

[0073] The mixed raw materials are heated and melted in a non-vacuum induction furnace, and stirred; after stirring, the mixed raw materials are allowed to stand and slag is removed to obtain an alloy melt; wherein the melting temperature is 1635°C, the amount of F2 type slag remover added is 0.35%, and the amount of silicon calcium particles added is 0.30%; the alloy is melted and allowed to stand for 1.25 minutes;

[0074] The alloy melt is poured into the tundish, and the alloy melt flows into the gas atomization chamber from the guide tube at the bottom of the tundish. The alloy melt is atomized by high-pressure nitrogen gas, and the alloy melt is broken into droplets. After cooling and solidification, the semi-finished powder is obtained by sedimentation. The alloy melt pouring temperature is 1595°C, the atomizing nitrogen pressure is 4.65MPa, the temperature inside the tundish is controlled at 1285°C, the guide tube is made of boron nitride, and the diameter of the guide tube is 5.5mm.

[0075] After the temperature drops to room temperature, the semi-finished powder is sieved using an ultrasonic vibration sieving machine with a 170-mesh sieve to obtain atomized sendustine soft magnetic powder.

[0076] Comparative Example 2

[0077] According to the proportion, FeSiAl alloy raw material, F2 slag remover and silicon-calcium particles are weighed; the FeSiAl alloy comprises the following components by weight percentage: 9.7% Si and 5.5% Al, the balance being Fe and other inevitable impurities, and the total content of impurity elements is less than 0.5%;

[0078] The FeSiAl alloy raw material is heated and melted in a non-vacuum induction furnace, and F2 slag remover and silicon-calcium particles are added and stirred; after stirring, the alloy is allowed to stand and slag is removed to obtain an alloy melt; wherein the melting temperature is 1650°C, the amount of F2 slag remover added is 0.35%, and the amount of silicon-calcium particles added is 0.30%; the alloy is allowed to stand for 1.25 minutes;

[0079] The alloy melt is poured into the tundish, and the alloy melt flows into the gas atomization chamber from the guide tube at the bottom of the tundish, and the alloy melt is atomized by high-pressure nitrogen to break the alloy melt into droplets. After cooling and solidification, the alloy melt is precipitated to obtain a semi-finished product powder; wherein, the alloy melt pouring temperature is 1625°C, the atomizing nitrogen pressure is 4.65MPa, the temperature inside the tundish is controlled at 1285°C, the guide tube is made of boron nitride, and the guide tube diameter is 5.5mm;

[0080] After the temperature drops to room temperature, the semi-finished powder is sieved using an ultrasonic vibration sieving machine with a 170-mesh sieve to obtain atomized sendustine soft magnetic powder.

[0081] The aerosolized iron-silicon-aluminum soft magnetic powders obtained in the above-mentioned embodiments 1 to 3 and comparative examples 1 and 2 were subjected to powder performance testing, and the powder performance testing items included Si content, Al content, tap density (TD), oxygen content (O), yield, micromorphology and production conditions; wherein the production conditions included yield, whether there was blockage and production efficiency; the yield refers to the percentage of the weight of the finished product part that meets the specific particle size requirements after the screening process to the total raw material weight; whether there was blockage was observed by observing whether there was blockage in the center package during the production process; and the production efficiency was evaluated by evaluating the time required for the entire production process of the aerosolized iron-silicon-aluminum soft magnetic powder. When the required time was 1 to 1.5 hours, the production efficiency was high, when the required time was 1.5 to 2 hours, the production efficiency was medium, and when the required time for the entire production process was greater than 2 hours, the production efficiency was low. The test results are shown in Table 1;

[0082] Table 1- Powder performance test results

[0083]

[0084] By comparing Examples 1 to 3 and Comparative Example 1, it can be seen that when pure iron, industrial silicon and aluminum ingots are used for mixed smelting, the smelting temperature needs to be higher, which makes it easy for the aluminum element to oxidize into slag, resulting in less Si and Al content in the atomized iron-silicon-aluminum soft magnetic powder, affecting the final performance of the product. In addition, the oxygen content increases, and there is more aluminum slag, which is prone to blockage.

[0085] By comparing Examples 1 to 3 and Comparative Example 2, it can be seen that if the pouring temperature of the alloy melt is too high, the oxygen content will increase, the aluminum slag will be more, and signs of ladle blockage will begin to appear.

[0086] The technical principle of the present invention is described above in conjunction with specific embodiments. These descriptions are only for explaining the principle of the present invention and cannot be interpreted as limiting the scope of protection of the present invention in any way. Based on the explanations herein, those skilled in the art can associate other specific embodiments of the present invention without creative work, and these equivalent variations or substitutions are all included in the scope defined by the claims of this application.

Claims

1. A method for preparing a gas-atomized sendust soft magnetic powder, characterized in that: The following steps are involved: Proportion: according to the proportion, weigh FeSiAl alloy raw material, slag remover and deoxidizer; Alloy smelting: heating and smelting the FeSiAl alloy raw material, adding a slag remover and a deoxidizer, and stirring; after stirring, standing and removing the slag to obtain an alloy melt; Gas atomization powder making: The alloy melt is poured into the tundish, and the alloy melt flows into the gas atomization chamber from the guide pipe at the bottom of the tundish. The alloy melt is atomized by high-pressure nitrogen gas, and the alloy melt is broken into droplets. After cooling and solidification, the droplets are precipitated to obtain semi-finished powder; Sieving: After cooling to room temperature, the semi-finished powder is sieved to obtain aerosolized Sendust soft magnetic powder.

2. The method for preparing a gas atomized sendust soft magnetic powder according to claim 1, characterized in that: In the proportioning step, the amount of the slag remover added is 0.15-0.35% of the total mass of the FeSiAl alloy raw material, and the amount of the deoxidizer added is 0.20-0.40% of the total mass of the FeSiAl alloy raw material.

3. The method for preparing a gas atomized Sendust soft magnetic powder according to claim 1, characterized in that: The commercially available model of the deslagging agent is F2 deslagging agent, and the deoxidizing agent is calcium silicon particles.

4. The method for preparing a gas atomized Sendust soft magnetic powder according to claim 1, characterized in that: In the step of alloy smelting, the alloy smelting temperature is 1600-1650° C., and the standing time is 0.5-2.5 min.

5. The method for preparing a gas atomized Sendust soft magnetic powder according to claim 1, characterized in that: In the gas atomization powder making step, the alloy melt pouring temperature is 1560-1620°C; the pressure of the high-pressure nitrogen is 4.0-5.0 MPa; and the temperature inside the tundish is 1200-1300°C.

6. The method for preparing a gas atomized Sendust soft magnetic powder according to claim 1, characterized in that: In the gas atomization powder making step, the material of the guide tube is boron nitride or zirconium oxide, and the diameter of the guide tube is 4.0-7.0 mm.

7. The method for preparing a gas atomized Sendust soft magnetic powder according to claim 1, characterized in that: In the sieving step, the particle size of the atomized Sendust soft magnetic powder is 165-180 meshes.

8. The method for preparing a gas atomized Sendust soft magnetic powder according to claim 1, characterized in that: The FeSiAl alloy comprises the following components by weight percentage: 7-12% Si and 4-8% Al, with the remainder being Fe and other inevitable impurities.

9. A gas atomized sendust soft magnetic powder, characterized in that: The aerosolized iron-silicon-aluminum soft magnetic powder is obtained by the preparation method of the aerosolized iron-silicon-aluminum soft magnetic powder as described in any one of claims 1 to 8, and the iron-aluminum-silicon alloy comprises the following components by weight percentage: 6-11% Si and 4-8% Al, and the balance is Fe and other inevitable impurities, wherein the other inevitable impurities include C, Mn, P and S, and by weight percentage, the content of the C element is <0.010%, the content of the Mn element is <0.35%, the content of the P element is <0.03%, and the content of the S element is <0.01%.

Citation Information

Patent Citations

  • Manufacturing method of high-magnetic-permeability low-power-consumption iron-silicon-aluminum alloy powder for magnetic powder cores

    CN103060677A

  • Process for preparing iron-silicon-aluminum powder and manufacturing magnetic core through non-vacuum gas atomization

    CN109202092A

  • Preparation method of atomized FeSiAl powder

    CN109317688A

  • Metal powder suitable for MIM injection molding ultrahigh-strength steel, preparation method and ultrahigh-strength steel

    CN116752055A

  • Deoxidizing and slagging-off method for producing low-oxygen stainless steel powder through water atomization

    CN117467819A